Cotton Research - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2016)
Cotton is the most important natural fiber crop of our planet, which provides humanity with cloth and vegetable oil, medicinal compounds, meal and hull for livestock feed, energy sources, organic matter to enrich soil, and industrial lubricants. Therefore, cotton research to improve sustainable cotton production worldwide is the vital task of scientific community to address the increasing demands and needs for cotton products. This Cotton Research book presents readers updated information and advances in current cotton science investigations. Chapters of this book provide the latest developments on cotton research and cover topics on cotton research infrastructure, physiology and agronomy, breeding and genetics, modern biotechnology, genomics and molecular breeding, crop management, and cotton-based product and textile researches.